Microscopic and molecular detection of Trichomonas vaginalis in outpatients seeking medical care in Upper Egypt - El-kareem, Nasser Mohamed Abd; Dyab, Ahmed Kamal; Albalawi, Nada Oudah; El Samea, Abdalla Abd; Taha, Mohamed Ahmed Ali; AlQadeeb, Hajar; Gareh, Ahmed; Hiekal, Elham Adel; Alzaylaee, Hind; Elmahallawy, Ehab Kotb (Frontiers in Microbiology, 2024)
IntroductionTrichomoniasis remains one of the most significant sexually transmitted disease (STDs) for public health. The disease is caused by parasitic protozoa, Trichomonas vaginalis (T. vaginalis), which is often underestimated in tropical medicine. Despite its public health importance, the epidemiology and molecular characteristics of trichomoniasis in Egypt remains poorly understood, particularly in the southern part of the country (Upper Egypt). This study targeted exploring the genetic variability of T. vaginalis infections in Egyptian women living in Upper Egypt using restriction fragment length polymorphism (RFLP).Patient and techniquesThis cross-sectional study included 150 female patients, who visited the gynaecology and obstetrics outpatient clinics at Sohag General Hospital between 2019 and 2022, exhibiting symptoms of trichomoniasis. Vaginal washout samples were collected from each patient and analyzed using three diagnostic techniques: direct wet mount microscopy, culture on TYM Diamond’s medium, and PCR amplification and Polymerase Chain Reaction-Restriction Fragment Length Polymorphism (PCR-RFLP) targeting the actin gene, which was applied to all 16 samples that tested positive in culture. The PCR-RFLP results were then visualized through agarose gels electrophoresis to detect DNA fragments.ResultsOut of 150 vaginal washout samples, 12 cases (8%) tested positive for T. vaginalis trophozoites via direct wet mount microscopy, while 16 samples (10.6%) were positive in culture. Additionally, PCR-RFLP analysis of the 16 culture-positive samples revealed that 13 samples were confirmed positive using this molecular method. The amplified products were digested with the restriction enzyme Hind II, yielding three DNA fragments of 60, 213, and 827 bp, which were then detected by agarose gel electrophoresis. Digestion with RsaI produced five fragments measuring 87, 103/106, 236, and 568 bp, while MseI digestion resulted in three distinct fragments of 204, 315, and 581 bp.ConclusionThis study provides robust baseline data on the prevalence and microscopic characteristics of T. vaginalis in Upper Egypt, while also presenting, for the first time, molecular detection and genotyping and revealed that genotype E is the only prevalent genotype in the region.